2016
DOI: 10.1111/1755-5922.12173
|View full text |Cite
|
Sign up to set email alerts
|

Non‐vitamin K Oral Anticoagulants Versus Warfarin for Patients with Atrial Fibrillation: Absolute Benefit and Harm Assessments Yield Novel Insights

Abstract: SUMMARYBackground and Objectives: Benefits and/or harms (including costs) of non-vitamin K oral anticoagulants (NOACs) versus warfarin therapy need appreciation in relative and absolute terms. Methods: Accordingly, we derived clinically relevant relative and absolute benefit/harm parameters for NOACs (apixaban, dabigatran, rivaroxaban, edoxaban) compared to warfarin from four clinical trials involving atrial fibrillation (AF) patients. For each trial, we tabulated patient numbers enduring four important outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 26 publications
0
12
0
1
Order By: Relevance
“…However, DOACs have greater acquisition costs. Thus, greater cost versus greater efficacy/safety profile and avoidance of monitoring have to be balanced [ 112 ]. A review of the use of DOACs in an elderly population with non-valvular AF demonstrated that they are beneficial and lead to a reduction of stroke risk in this population [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, DOACs have greater acquisition costs. Thus, greater cost versus greater efficacy/safety profile and avoidance of monitoring have to be balanced [ 112 ]. A review of the use of DOACs in an elderly population with non-valvular AF demonstrated that they are beneficial and lead to a reduction of stroke risk in this population [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…In China, three NOACs (rivaroxaban, dabigatran and apixaban) were approved sequentially for clinical use since 2009. Considering the high price of NOACs in China, the costutility of NOACs should be carefully re-evaluated [8]. It can be foreseen that there is a great demand of NOACs in China due to the high burden of diseases needing anticoagulation therapy [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, patients with a high risk of relapse, such as those with cancer, must pay the cost of NOACs by themselves after the first 6 months and the actual prescription rate of NOACs after the first 6 months cannot be identified using the Korean Health Insurance Review and Assessment Service (HIRA) databases. 12 Absolute benefits and harms of NOACs in NVAF patients using the number needed to treat (NNT) and/or number needed to harm (NNH) were addressed in several reports including a study conducted by Kumana et al 122 Kumana et al showed absolute benefits of NOACs for primary-outcome prevention were modest in terms of NNT/year value (eg, 182-481, Table 3) with greater acquisition costs compared to warfarin. 122 However, these findings should be considered with benefits from avoidance of INR monitoring and its impact on the quality of life, etc.…”
Section: Adherence and Persistence Of Noacsmentioning
confidence: 99%
“…12 Absolute benefits and harms of NOACs in NVAF patients using the number needed to treat (NNT) and/or number needed to harm (NNH) were addressed in several reports including a study conducted by Kumana et al 122 Kumana et al showed absolute benefits of NOACs for primary-outcome prevention were modest in terms of NNT/year value (eg, 182-481, Table 3) with greater acquisition costs compared to warfarin. 122 However, these findings should be considered with benefits from avoidance of INR monitoring and its impact on the quality of life, etc. 122 Therefore, we need to focus on the long-term cost-effectiveness of NOACs.…”
Section: Adherence and Persistence Of Noacsmentioning
confidence: 99%
See 1 more Smart Citation